Mobile application for the prevention and self-care of varicose veins - Andrade-Arenas, Laberiano; Retuerto, Margarita Giraldo; Yactayo-Arias, Cesar (Institute of Advanced Engineering and Science, 2024)
Details the process of creating a prototype of a mobile application designed to promote prevention and self-care of varicose veins in patients at high vascular risk. The objective is to investigate the experience of patients at high vascular risk when using a mobile application created for the prevention and self-care of varicose veins. The methodology used is design thinking, a user-centered approach that seeks to solve complex challenges through creativity, design and problem solving. The results obtained from the expert judgment, based on ATLAS.ti 23, provide valuable insight into the feasibility and potential of the technological tools as the interface has the highest variability among the criteria evaluated, followed by interaction and quality, while usability presents the lowest variability. This suggests that usability evaluations tend to be more consistent compared to the other criteria. In conclusion, the present work analyzes how mobile applications can play a crucial role in promoting prevention and self-care of varicose veins in patients at high vascular risk. The good reception of the prototype confirms the importance of technology in the field of vascular health and highlights the value of this approach to improve quality of life and health management in this demographic group.